PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENS UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA - Lundeto, Rahmatia; Pateda, Lamsike; Iskandar, Karmila (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2024)
AbstractThis research aims to determine the increase in student learning activity after implementing the Teams Games Tournament (TGT) learning model in class 1V Indonesian language learning. This research was conducted in class IV at SDN 3 Limboto using classroom action research. Learning is carried out in 2 cycles. Each cycle has stages, namely: planning, implementation, observation and reflection. The subjects of this research were 38 class IV students at SDN 3 Limboto. Data collection techniques were carried out using observation and test techniques. The data analysis technique used in this research is descriptive statistics. The results of the research show that teacher activity and student activity in the learning process by applying the Teams Games Tournament model in Indonesian language learning material with the word